The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1161/01.str.0000109772.64650.18
|View full text |Cite
|
Sign up to set email alerts
|

Hemicraniectomy for Massive Middle Cerebral Artery Territory Infarction

Abstract: Background and Purpose-Hemicraniectomy and durotomy have been proposed in many small series to relieve intracranial hypertension and tissue shifts in patients with large hemispheric infarcts, thereby preventing death from herniation. Our objective was to review the literature to identify patients most likely to benefit from hemicraniectomy. Methods-All available individual cases from the English literature were reviewed and analyzed to determine whether age, vascular territory of infarction, side of infarction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
257
6
21

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 327 publications
(297 citation statements)
references
References 37 publications
(37 reference statements)
13
257
6
21
Order By: Relevance
“…Several studies have reported that age should be considered an important factor in patients to be submitted to the surgical procedure 15,16,17 . The decision for patients over 60 years of age must be individualized: there is great controversy regarding this cut-off point, as some authors describe benefits beyond this age-group 12,15,18,19 , while others report unfavorable outcomes 6,7,8,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that age should be considered an important factor in patients to be submitted to the surgical procedure 15,16,17 . The decision for patients over 60 years of age must be individualized: there is great controversy regarding this cut-off point, as some authors describe benefits beyond this age-group 12,15,18,19 , while others report unfavorable outcomes 6,7,8,9 .…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial pressure monitoring, mannitol or hypertonic saline may be unsuccessful, and evidence supporting emergency decompressive craniectomy is emerging. 113 The procedure may be life-saving if done early in cases of impending herniation, is associated with good outcomes in young stroke patients, 114 and is supported by published guidelines. 79 Anticipated surgical intervention for malignant cerebral edema might also influence the acute treatment choice towards the more easily reversible UFH rather than LMWH or ASA.…”
Section: Acute Treatment: Supportive Care and Prevention Of Secondarymentioning
confidence: 91%
“…Вмешательство получило название декомпрессивной гемикраниоэктомии или декомпресси-онной краниоэктомии, в русскоязычном варианте -де-компрессионной трепанации черепа (ДТЧ) [3]. На на-чальном этапе эта операция использовалась, главным образом, у больных с черепно-мозговой травмой [4], но затем ее начали применять и при других заболеваниях, сопровождающихся выраженным отеком мозга, прежде всего -при обширном ишемическом инсульте в бассей-нах внутренней сонной или средней мозговой артерий [5], а затем -при внутричерепном кровоизлиянии анев-ризматического генеза [6].…”
Section: список сокращенийunclassified